India - Taking Agriculture to the Market - World Bank (Washington, DC, 2012)
Policy makers in India recognize the importance o f well-functioning markets to agricultural growth, food security, and broad-based rural development. Markets facilitate the commercialization and diversification of farming, and they are essential for efficiently bringing food and agricultural products to domestic and international consumers. Well functioning domestic markets can reduce the cost of food and assure stability of supply, which as the recent global food crisis has highlighted, are key to assuring the food security of poor and non-poor households. They also open opportunities for greater value-addition and employment throughout the economy. The rapid growth of the Indian economy is bringing new forces for change in agricultural marketing and processing systems. Changes in consumer demand are fueled by rising incomes, increasing urbanization, a growing middle class demanding more diversified and higher-quality food, more working women demanding access to prepared or processed foods and more convenient shopping under one roof, and increased exposure to products through wider media penetration (domestic and international television, cable, and internet). These forces in turn drive changes in the structure of marketing and encourage agricultural diversification.